Using position control to improve the efficiency of wind turbine - Roshen Tariq Ahmedhamdi; Salam Waley Shneen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Wind energy is one of the renewable energies that can be using to generate electricity. Increasing demand for this type of renewable energy for sustainability and accessibility. Environmentally as it does not cause any pollution in addition to the abundance of required equipment and lessmaintenance and long operation life of its parts despite the high cost of the system at its installation but at long term, become cheaper. Wind power generators depend on their operation on wind speed and direction. Therefore,it should be installing in places where the wind speed is adequate and sufficient to rotate its rotor, it knows that wind speed is variable in its speed and direction they change every hour and every season. In this design, many practical and theoretical (simulation) experiments have been done which will be mentioned and explained in details in this research shows that this mechanism raises the efficiency of wind power generators by 80% when the rotor of the wind turbine directed towards the wind than if they were fixed direction.